The Effect of Video Media-Based Jigsaw Type Cooperative Learning Model to Increase Motivation and Science Learning Outcomes - Rahayu, Sri; Annur, Saipul; Diki, Diki (Jurnal Sustainable, 2023)
The purpose of this research is to ascertain whether or not the Jigsaw method, which makes use of video media, improves the scientific motivation and cognitive learning results for fifth graders at SDN 2 Tekorejo. One component of the quantitative approach used in this research is the genuine experiment design technique. The experimental group and control group were selected using simple random selection from all fifth graders in five public primary schools in the Melati Cluster, Buay Madang Timur District, East OKU. Instruments for data collecting include surveys, exams, and observations; tests for normality and homogeneity, as well as independent t-tests, t-test samples, and gain tests, are used for data analysis. Students' levels of intrinsic desire to learn were found to be 0.49 in the control group and 0.78 in the experimental group, according to the N-Gain test. The experimental group's N-Gain test for cognitive learning outcomes was 0.65, but the control group's was just 0.43. Students' motivation and cognitive learning results were improved in the video-assisted jigsaw method class compared to the lecture method control class. It follows that students' motivation and cognitive learning results are impacted by the Jigsaw method with video media assistance.